Curriculum Implementation Integral Education Based on Tauhid (Case Study of Curriculum Implementation in SMA Luqman Al Hakim Surabaya) - Din Muhammad Zakariya (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2019)
This study aims to explore how the design of Integral based Tauhid Education curriculum in SMA Luqman Al Hakim Surabaya, how to implement it, and how to improve the quality of education. The type of approach in this study is descriptive qualitative, as the direction of the type of qualitative research, then the data collected were analyzed to obtain various interpretative descriptions according to the logical and rational scientific research rules on the data collected. The results of this study can be summarized as follows. 1) The curriculum of Tauhid-Based Integral Education in SMA Luqman Al Hakim Surabaya is a blend curriculum of curriculum 2013. 2) The implementation of Tauhid-Based Integral Education Curriculum using three approaches that serve as references, first, Tilawah Method, second, Tazkiyah Method, and Third, Ta'limah Method. Curriculum development contains three characteristics, namely politeness priority before science, thorough and aligned, and back to nature. The implementation of the Tauhid-Based Integral Curriculum in SMA Luqman Al Hakim Surabaya is described in the structure and content of the curriculum, setting the learning load and time allocation, learning completeness, appraisal system, increase, graduation, and life skills education. 3. The implementation of Tauhid-Based Integral Education Curriculum in improving the quality of education in SMA luqman Al Hakim Surabaya, through the preparation of human resources who have qualifications in their field and have the spirit to preach through education. The three characters of the students’ output from the curriculum of Tauhid-Based Integral Education are, first Taqwa, second Intelligent, and third independent. Keywords: Curriculum Implementation, Integral Education, Tauhid-Based